Analysis of the road connectivity: A case study in the Tietê-Jacaré Hydrographic Basin – SP, Brazil - Trevisan, Diego Peruchi; Moschini, Luiz Eduardo (Brazilian Journal of Science, 2022)
The structures and dimensions of anthropized areas undergo a growing process of modification, where man-made land spaces unevenly alter their nature and composition, requiring a new definition and understanding of their boundaries. This transformation is a consequence of established socio-environmental, economic, and cultural relations. This work contemplates the evaluation of road connectivity present in the territory of the Tietê-Jacaré Hydrographic Basin - SP, through the application of the Integration Space Syntax indices, with the objective of evaluating the dynamic and temporal process of the road infrastructures in 2007 and 2017. Geographic Information Systems (GIS) techniques were used using the integration theory to investigate the road connection, applying the “Groups” tool that showed the connections based on the “pixel” analysis of the images generated by the Overlay tool. The axial map was elaborated, consisting of the analysis of the road network connections, considering all possible straight segments (axial lines) allowing the understanding of the road network connectivity in the Tietê-Jacaré Hydrographic Basin. By updating the road network, growth from 9,450.43km from 2007 to 13,082.88km in 2017 was observed, totaling an increase of 38.43%. The watershed increased road network in all regions, which eventually led to changes in road integration patterns, increasing the number of road network connections by almost one third (from 67,125 to 81,895). These factors should be analyzed detailed, mainly related to the future and quality of urban resources and territorial planning, both municipal and regional.